Tinjauan Maslahah Mursalah Terhadap Tajdid Nikah Pasutri Beda Agama: Studi Kantor Biro Taaruf Syar’i Kabupaten Sukoharjo - Nahar Surur (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2022)
This study aims to determine the practice of organizing tajdid marriages at the Taaruf Syar'i Bureau office, Sukoharjo district. In addition, the author also examines from the perspective of mas}lah}ah mursalah regarding what has been attempted by the Taaruf Syar'i Bureau Office in Sukoharjo Regency against interfaith couples in conducting tajdidun marriages. This research is a field research, which is a data collection technique carried out by means of field interviews by asking questions to married couples of different religions and collecting several other sources such as theses, theses, papers, journals, website articles, and news. To strengthen the research data, interviews were conducted with the head of the Ta'aruf Syar'i Bureau, Sukoharjo district, who gave a decision regarding the research title. The results of the researcher's analysis can be concluded that the Head of the Ta'aruf Bureau takes the Tajdid Nikah decision for married couples who initially marry in a Christian way and then want an Islamic marriage, in line with the mas}lah}ah mursalah principle, which is to continue their marriage and their marriage is legal in Islam. . With the Tajdid Marriage, the benefits taken are greater than the harm caused.